Introduction to malaria - Warhurst, David (Henry Stewart Talks, 2010)
Malaria parasites of man, Species of Plasmodium, Life cycle of malaria, Malaria: the problem, Climatic and seasonal constraints, Stable and unstable malaria, Malaria control: transmission and morbidity, Prevention of man/mosquito contact, Prompt diagnosis and drug treatment, How does the infection persist?, P. vivax and P. Ovale, Hematin, Falciparium malaria, Malaria in pregnancy, Innate immunity to malaria, RBC enzyme deficiencies, Acquired immunity, Vaccines
Archived at 2016/12/28